2023
DOI: 10.1101/2023.05.16.541055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing AlphaFold-Multimer-based Protein Complex Structure Prediction with MULTICOM in CASP15

Abstract: AlphaFold-Multimer has emerged as the state-of-the-art tool for predicting the quaternary structure of protein complexes (assemblies or multimers) since its release in 2021. To further enhance the AlphaFold-Multimer-based complex structure prediction, we developed a new quaternary structure prediction system (MULTICOM) to improve the input fed to AlphaFold-Multimer and evaluate and refine the outputs generated by AlphaFold2-Multimer. Specifically, MULTICOM samples diverse multiple sequence alignments (MSAs) an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Other ways of improving MSA usage by AFM have also been proposed [63] and could be combined with advances in pairing. Besides improving MSA construction [64] and the extraction of MSA information, other promising approaches include exploiting structural alignments [65], using massive sampling and dropout [66], and combining AFM with more traditional docking methods [67,68], which has allowed e.g. to improve structure prediction of 6A6I [67].…”
Section: Discussionmentioning
confidence: 99%
“…Other ways of improving MSA usage by AFM have also been proposed [63] and could be combined with advances in pairing. Besides improving MSA construction [64] and the extraction of MSA information, other promising approaches include exploiting structural alignments [65], using massive sampling and dropout [66], and combining AFM with more traditional docking methods [67,68], which has allowed e.g. to improve structure prediction of 6A6I [67].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced ML techniques are being applied to rapidly solve structural biology problems [55][56][57]. By reviewing the literature, we found that ML is widely used in methods to predict the impact of GV on protein structure.…”
Section: Based On Machine Learningmentioning
confidence: 99%
“…AlphaFold-multimer predictions--We used Alphafold-multimer v2.3.1, 3D models of the human LRRK2-RAB10 complex. The necessary databases for running AlphaFold-multimer were downloaded on 12 January 2023 (Liu et al, 2023).…”
Section: Analysis Of the Model Ensemble--mentioning
confidence: 99%